Thermogravimetric and Biological Studies of Organotin(IV) Complexes with 4-(Hydroxymethyl)piperidine-1-Carbodithioic Acid: Thermogravimetric and Biological Studies of Organotin (IV) - Hussain, Shabbir; Ali, Saqib; Shahzadi, Saira (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Present studies were conducted to perform thermogravimetric characterization and biological activity investigations of organotin dithiocarbamates of general formulae R3SnL (R = n-Bu, 1; Ph, 2; Cy, 3), R2Sn(Cl)L (R = Me, 4; Ph, 5) and R2SnL2 (R = Me, 6) where L = 4-(hydroxymethyl)piperidine-1-carbodithioate. A novel procedure was also developed for the synthesis of product 2 by direct reflux of 4-(hydroxymethyl)piperidine-1-carbodithioic acid (HL) with triphenyltin(IV) hydroxide. HL was decomposed at low temperatures as compared to the metal complexes. The coordinated products were degraded leaving behind the tin or SnOCl inorganic residues. The products1-6 have shown excellent antimicrobial activities against the tested bacterial (Escherichia coli, Salmonella typhi, Staphylococcus aureus, and Bacillus subtilis) and fungal (Fusarium solani, Aspergillus niger, Alternaria solani, and Fusarium verticillioides) strains. The biological activities were found to depend upon the substitution pattern at the central tin atom.